The relationship between cumulative family risk and athlete burnout among Chinese college athletes: the mediating role of negative affect - Li, Rui; Guo, Xujuan; Liang, Yuqian; An, Yalun; Xu, Maoyao; Zhang, Biao (Frontiers in Psychology, 2023)
This study explored the relationship between cumulative family risk and athlete burnout of Chinese college athletes, and the mediating effect of negative affect (NA) on the relationship between cumulative family risk and athlete burnout. The questionnaire survey was conducted with 824 students from more than 40 universities in China. We found that cumulative family risk was significantly positively correlated with athlete burnout (r=0.12, p < 0.001) and negative affect (r=0.12, p < 0.001), and negative affect was significantly positively correlated with athlete burnout (r=0.35, p < 0.001). Negative affect played a mediating role between cumulative family risk and athlete burnout. Conclusion: Family cumulative risk has a negative impact on athlete burnout in college students through the mediating effect of negative affect. At the same time, this paper also discusses the practical significance of revealing the athlete burnout of college students.